Narrativas como fontes de conhecimento: da relação com o saber à construção do ser professor e professora em Araguaína-TO - Cardoso, Bruna da Silva (2018)
This dissertation investigated narratives, considered as sources of knowledge, to understand the relationship with knowledge, with the school and with the construction of being a teacher, in life histories of four teachers from Araguaína-TO. It was characterized as a qualitative investigation which used the methodology of oral history and used the semi-structured interviews as a technique for constructing narratives of life history. It was dialogued with the following theoretical-methodological reference: Alberti (2006), Arroyo (2013), Bragança (2012), Charlot (1996, 2000, 2001, 2002, 2005, 2011), Josso (2004), Portelli (1996, 1997, 2010, 2016), Tardif (2011), Thompson (1992, 2006) and Tuan (2013). As contributions of the research, it was emphasized that teachers are knowledge-producing subjects and they are not just reproducers of ready-made knowledge, elaborated by third parties. From the systematization and spatialization of life histories, it showed that the formation runs through various spaces / places and subjects that have proved their importance in the teaching trajectories. The narratives had an emancipatory character, since the teachers were considered the protagonists in the investigation and narrated their learning to characterize the knowledge to be a teacher, observing how the relation with knowledge, with the school and the university were fundamental in this. process. The narratives of knowing how to be a teacher identified teaching as a profession of challenges, difficulties and possibilities, emphasizing that each one builds his|her own formation and, by socializing it, it can inspire the trajectory of other peers. Therefore, the narratives of teachers in their human, political and cultural dimensions were sources of knowledge about the relationship with the knowledge and construction of being a teacher, they are elaborated and meaningful from their profession and life experiences.